Metabolomic and Genome‐wide Association Studies Reveal Potential Endogenous Biomarkers for OATP1B1. Issue 5 (20th September 2016) - Yee, SW; Giacomini, MM; Hsueh, C‐H; Weitz, D; Liang, X; Goswami, S; Kinchen, JM; Coelho, A; Zur, AA; Mertsch, K; Brian, W; Kroetz, DL; et al.
Abstract : Transporter‐mediated drug‐drug interactions (DDIs) are a major cause of drug toxicities. Using published genome‐wide association studies (GWAS) of the human metabolome, we identified 20 metabolites associated with genetic variants in organic anion transporter, OATP1B1 ( P < 5 × 10 −8 ). Of these, 12 metabolites were significantly higher in plasma samples from volunteers dosed with the OATP1B1 inhibitor, cyclosporine (CSA) vs. placebo (q‐value < 0.2). Conjugated bile acids and fatty acid dicarboxylates were among the metabolites discovered using both GWAS and CSA administration. In vitro studies confirmed tetradecanedioate (TDA) and hexadecanedioate (HDA) were novel substrates of OATP1B1 as well as OAT1 and OAT3. This study highlights the use of multiple datasets for the discovery of endogenous metabolites that represent potential in vivo biomarkers for transporter‐mediated DDIs. Future studies are needed to determine whether these metabolites can serve as qualified biomarkers for organic anion transporters. Quantitative relationships between metabolite levels and modulation of transporters should be established.